Construction Of Gender Role In Advertising Kecap ABC Version "Kecap ABC Help True Husband Respect Wife" - Mufadhilatul Hidayah; Poppy Febriana (Indonesian Journal of Cultural and Community Development, 2022)
Gender construction has resulted in comparisons between men and women. The difficulty in distinguishing gender characteristics is due to the long process of socialization and construction. Just like the gentle women, on the other hand, the mighty men, constructed by citizens or biological natures based on God's decree. This construction then gives rise to divisions of work roles between men and women. This research is a type of descriptive qualitative research using the semiotic analysis method of Charles S. Peirce. Semiotic analysis of Charles S. Peirce To explain the icon, index and symbol in the ABC Soy Sauce Advertisement version of "ABC soy sauce helps real husbands respect their wives". The results of this study indicate that women are not completely free from their stereotypes. The role of women is always depicted as a figure who only works in the domestic sphere so that the space for movement is very limited.